Investigating communicative language teaching through meaning-based tasks and processing strategies to strengthen learners’ oral performance - Ahmad Tauchid; Ahmad Muhid; Amin Khudlori; Nenin Astiti Ayunda; Aaron Lee; Choi Jisoo (Early Publishing Group, 2025)
Developing learners’ oral proficiency remains a persistent issue in EFL settings, where limited opportunities for authentic communication restrict students’ ability to express ideas fluently and confidently. This study investigates how meaning-based communicative tasks, together with learners’ processing tendencies, contribute to measurable improvements in spoken performance. Using a structured pre-test–post-test design, the research involved 30 first-year vocational college students who completed a six-week instructional program consisting of role-plays, information-gap activities, picture-based narratives, and guided opinion exchanges. Data were gathered through standardized oral performance tests administered before and after the intervention and evaluated by trained raters using a rubric assessing fluency, pronunciation, vocabulary, and grammar; instructional logs were maintained to ensure consistency in task delivery. All numerical data were analyzed using SPSS to compare pre-test and post-test scores and to determine the magnitude and significance of performance changes. The findings reveal a clear increase in learners’ oral performance, reflected in smoother delivery, more accurate and varied language use, and stronger coherence in expressing ideas, with learners who demonstrated stronger meaning-focused processing tendencies showing comparatively greater improvement. The study concludes that aligning meaning-based communicative tasks with learners’ natural processing strengths creates instructional conditions that effectively accelerate oral proficiency development, implying that pedagogical planning should integrate communicative tasks that stimulate meaningful interaction while supporting learners’ processing preferences to enhance spoken language learning outcomes.